The rise of Novgorod revisited - Musin, Aleksandr (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2018)
This article deals with the problem of the cultural, political and ethnic characteristics of the first settlers of Novgorod. The previous historiography is critically reviewed. The reappraisal of the archaeological reports and collections of 1950s-2000s years significantly increases the number and categories of Scandinavian objects, while the Slavonic component of early Novgorod remains unclear. The Scandinavians should be counted among the founders and first settlers of Novgorod as early as 930-950 A.D. The pattern of the distribution of Scandinavian and Scandinavian-like objects suggests a free resettlement of Norsemen in the town. They arrived there directly form the North, and not from the Middle Dnieper area inhabited by the Rus’-Rhôs, an ethno-social group which was a result of the acculturation of the Scandinavians in the East-European milieu. The tradition of Russian historiography to deny the participation of Scandinavians in the early development of Novgorod takes its origin from the “auto-censorship” of the Soviet period, it later continued thanks to “scientifi